Defining osteoarthritis of the hand for epidemiological studies: the Chingford Study. Issue 4 (April 1994) - Hart, D; Spector, T; Egger, P; Coggon, D; Cooper, C
Abstract : OBJECTIVES–To explore the relative merits of clinical and radiological examination in defining hand osteoarthritis (OA) for epidemiological purposes. METHODS–A total of 976 women aged 45-64 years were selected from the general population and underwent a structured interview, clinical examination of the hand joints and radiography of the hands and knees. The inter-relationship of the clinical and radiological findings was examined, and also the association of each with hand symptoms and the presence of knee OA. RESULTS–Clinical and radiographic signs of hand OA generally correlated with each other, and each was associated with hand symptoms to a similar degree. When analysed in combination, they were only marginally better at predicting symptoms than when tested individually. However, when they were examined in relation to radiographic features of knee OA, there was a significantly stronger association with radiographic features of hand OA than with clinical features. CONCLUSIONS–Hand radiology provides a better overall assessment of osteoarthritis than physical examination of the interphalangeal joints or carpo-metacarpal joint; in situations where radiology is not available clinical examination is a viable substitute.